2020
DOI: 10.1155/2020/3961735
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Involvement in the Modulation of the Glioblastoma Environment

Abstract: Glioblastoma (GBM) is the most deadly primary brain tumour and is a paradigmatic example of heterogeneous cancer. Although expanding data propose the phenotypic plasticity exhibited by glioblastoma cells, as a critical feature involved in the tumour development and posttherapy recurrence, the central machinery responsible for their aggressiveness remains elusive. Despite decades of research, the complex biology of the glioblastoma is still unknown. Progress in genetic and epigenetic discoveries has improved di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 93 publications
0
6
0
1
Order By: Relevance
“…Although multiple drug delivery vehicles (liposome, polymeric nanoparticle, solid lipid, and polymeric micelle) have been developed in cancer therapy, it is very challengeable to use these synthesized nanoparticles in GBM treatment due to the issues of stability and/or the BBB [ 29 ]. As a natural vesicle, EV has multiple advantages over the synthesized particles, including low immune toxicity, high stability, and efficient penetration of the BBB [ 36 , 37 ]. This study used our established biomanufacturing platform [ 28 , 38 ] to generate EV from human cell line, surface-tagged mAb, and the packed drug Ver-A, which demonstrated the capabilities of high GBM targeting and effective drug delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multiple drug delivery vehicles (liposome, polymeric nanoparticle, solid lipid, and polymeric micelle) have been developed in cancer therapy, it is very challengeable to use these synthesized nanoparticles in GBM treatment due to the issues of stability and/or the BBB [ 29 ]. As a natural vesicle, EV has multiple advantages over the synthesized particles, including low immune toxicity, high stability, and efficient penetration of the BBB [ 36 , 37 ]. This study used our established biomanufacturing platform [ 28 , 38 ] to generate EV from human cell line, surface-tagged mAb, and the packed drug Ver-A, which demonstrated the capabilities of high GBM targeting and effective drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…These delivery vehicles have been limited in clinic application due to the poor stability, limited loading capacity, toxicity or reduced efficacy because of BBB. Recent studies showed that extracellular vesicle (EV), a natural endogenous nanoparticle, has great potential for targeted delivery of highly potent drugs with the advantages of immune tolerance, circulation stability, capability to cross BBB, and tumor targeting via surface-tagged GBM-targeted reagents [ 36 , 37 ]. Our previous studies have established the platform of EV biomanufacturing and surface tagging [ 38 ] and demonstrated its capability of targeted delivery of combined therapies [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that macrophages could change the tumor microenvironment to promote cell invasion and mediate the paraptosis by oxidative stress in glioma cells. Extracellular vesicles have multiple functions in the central nervous system and are closely related to the communication between cell types within glioblastoma and their microenvironment [ 29 ]. Glioblastoma-induced exosomes can increase the oxidative stress of cerebellar neurons by reducing cellular antioxidant defense and increasing oxidative damage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that EVs, signaling vehicles with multifaceted functions in neuronal and glial crosstalk, have a crucial role in the communication among cell types within glioblastoma and its microenvironment [34,35]. EVs are membrane-enclosed nanospheres that contain proteins, lipids, and nucleic acids, such as DNA, mRNA, and noncoding RNAs, and are released by most cells [36,37].…”
Section: Ev-mediated Communication Between Astrocytes and Glioblastomamentioning
confidence: 99%